Recombinant DnaK Orally Administered Protects Axenic European Sea Bass Against Vibriosis - Yaacob, Eamy Nursaliza; Norouzitallab, Parisa; De Geest, Bruno G.; Bajek, Aline; Dierckens, Kristof; Bossier, Peter; Vanrompay, Daisy (Frontiers in Immunology, 2020)
Abstract Vibrio anguillarum causes high mortality in European sea bass (Dicentrarchus labrax) larviculture and is a hindering factor for successful sustainable aquaculture of this commercially valuable species. Priming of the innate immune system through administration of immunostimulants has become an important approach for controlling disease outbreaks in marine fish larviculture. This study was conducted to evaluate immunostimulation by Escherichia coli HSP70 (DnaK) in axenic European sea bass larvae in order to protect the larvae against vibriosis. DnaK stimulates the immune response in crustaceans and juvenile fish against bacterial infections. The use of axenic fish larvae allows studying immunostimulation in the absence of an interfering microbial community. At 7 days post-hatching, larvae received a single dose of alginate encapsulated recombinant DnaK. Two non-treated control groups in which animals either received empty alginate microparticles (C1) or no alginante microparticles (C2 and C3) were included in the study. Eighteen hours later, all larvae, except the ones from group C3 (non-infected control) were challenged with V. anguillarum (105 CFU, bath infection). Mortality was daily recorded until 120 h post infection and at 18, 24 and 36 h post infection, larvae were sampled for expression of immune related genes. Results showed that V. anguillarum induced an immune response in axenic sea bass larvae the innate immune response was incapable of protecting the larvae against deadly septicaemic disease. In addition, we showed that administration of alginate encapsulated DnaK to axenic European sea bass larvae at DAH7 resulted in a significant, DnaK dose dependent, upregulation of the immune sensor, regulatory and effector genes. Significant upregulation of cxcr4, cas1 and especially of hep and dic was correlated with significant higher survival rates in V. anguillarum infected larvae. In the future recombinant DnaK might perhaps be used as a noval immunostimulant in sea bass larviculture.